Analisis dan Perancangan Human Resource Information System (HRIS) pada Universitas Tanri Abeng - Sipahutar, Ayub Boy Sandi; Widyaningsih, Tri Wahyu (Jutis (Jurnal Teknik Informatika), 2023)
Abstract—Data management in the human resources division is an important matter in every agency, because it can measure employee performance. After analyzing the system currently running at Tanri Abeng University, an information system called HRIS was developed. HRIS is a web-based information system developed using the Waterfall method and using the UML (Unified Modeling Language) design. The system developed can assist HRD managers in managing and processing employee data, educators, and educational staff such as profile data, leave and permits, attendance, to income calculations. HRIS has carried out the stages of testing by the end user, namely the HRD manager and black box testing.